MEDIATISASI HUBUNGAN PENDIDIKAN ISLAM DALAM KELUARGA PADA ERA DIGITAL (PERSPEKTIF AL-QURAN SURAT LUQMAN AYAT 12-19) - Dwi Wulan Sari (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah dan Keguruan UNSIQ Jawa Tengah, 2022)
Technological advances that continue to develop have a negative and positive affect on the world of Islamic education in the family. Previously, conversations could only be done person to person, but now it can be done online. As a result, families have to race against the media, which is difficult to control. The methods the authors used in this research is qualitative through a literature study research model that uses research data sources from documents in the form of books, scientific articles, reviews or previous research results. The study of Luqman's letter verses 12-19 was carried out as a way to sharpen the discussion regarding the relationship between Islamic education and the role of the family in facing the digital era. Based on Luqman's letter, verses 12-19, there are several values ​​of Islamic education that need to be applied in the digital era, namely: monotheism, morality, worship (ubudiyah), social, mental and exemplary. The steps for planting education include; First, the cultivation of faith or faith education. Second, religious education such as prayer, fasting and reading the Koran. Third, moral education. The development of the digital era still places parents as the main actors in providing Islamic education in the family. The development of the digital era requires parents to consistently maintain their children's nature, instill faith, straighten and motivate children, and provide good information. So, no matter how strong the current, the child will remain strong and not fall into bad things.